1983
DOI: 10.1093/bja/55.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Effects of Infusions of Diisopropyl Phenol (Ici 35 868) During Nitrous Oxide Anaesthesia in Man

Abstract: The haemodynamic effects of diisopropyl phenol in cremophor EL at infusion rates of 50-55 and 100 micrograms kg-1 min-1 in combination with inhalation of 67% nitrous oxide have been studied during spontaneous and controlled ventilation in patients premedicated with morphine and atropine. Under all the conditions studied diisopropyl phenol supplementation of nitrous oxide anaesthesia was associated with a decreased arterial pressure (-20% to -31%) compared with the awake patient, related to a decrease in cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1

Year Published

1986
1986
1996
1996

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(19 citation statements)
references
References 13 publications
3
15
1
Order By: Relevance
“…In contrast to previous studies which, in general, reported a decrease in heart rate (con comitant with a decrease in arterial blood pressure) during propofol anesthesia [1], the basic SCL decreased (i.e., an increase in heart rate) transiently from 565 ± 36 ms at baseline to 527 ± 26 ms after high-dose propofol (p < 0.05). The reported effects of propofol on the heart rate have not been uniform: some investigators have described an increase [17,18], whereas others have observed a decrease [19] or minimal or no change [20,21] in heart rate. The reason for these different results is not clear, but may, in part, reflect differences in autonomic tone and the concomitant use of other anesthetic agents [4][5][6][7][8][9]22] Clinically, propofol has been reported to occasionally cause profound sinus bradycardia [4][5][6][7][8], often persisting into the postoperative period [4], and asystolic cardiac arrest [5][6][7][8], especially when used in combination with potent opioid agents [4][5][6][7][8][9]22], Although less frequently, propofol has also been reported to cause significant AV block, resulting in cardiac arrest [9], However, with the exception of published case reports [4][5][6][7][8][9], significant bradyarrhythmias, in general, have not been seen in large number of patients exposed to propofol for a variety of procedures [22,…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies which, in general, reported a decrease in heart rate (con comitant with a decrease in arterial blood pressure) during propofol anesthesia [1], the basic SCL decreased (i.e., an increase in heart rate) transiently from 565 ± 36 ms at baseline to 527 ± 26 ms after high-dose propofol (p < 0.05). The reported effects of propofol on the heart rate have not been uniform: some investigators have described an increase [17,18], whereas others have observed a decrease [19] or minimal or no change [20,21] in heart rate. The reason for these different results is not clear, but may, in part, reflect differences in autonomic tone and the concomitant use of other anesthetic agents [4][5][6][7][8][9]22] Clinically, propofol has been reported to occasionally cause profound sinus bradycardia [4][5][6][7][8], often persisting into the postoperative period [4], and asystolic cardiac arrest [5][6][7][8], especially when used in combination with potent opioid agents [4][5][6][7][8][9]22], Although less frequently, propofol has also been reported to cause significant AV block, resulting in cardiac arrest [9], However, with the exception of published case reports [4][5][6][7][8][9], significant bradyarrhythmias, in general, have not been seen in large number of patients exposed to propofol for a variety of procedures [22,…”
Section: Discussionmentioning
confidence: 99%
“…Increases in arterial inflow to the forearm will increase the rapidity of the stabilization of forearm vein pressure during each venous occlusion (as noted in Figure 1) but should not influence the absolute change in forearm volume. Moreover, in several studies (3,(5)(6)(7)19) propofol has been shown to reduce myocardial function, although in some cases these changes in myocardial function could be attributed to reductions in cardiac preload. We do not wish to exclude this mechanism as an additional contributor to the hypotension noted during administration of propofol.…”
Section: Discussionmentioning
confidence: 99%
“…When propofol has been used for induction of anesthesia, a recurring observation has been that the hemodynamic responses, particularly the decrease in arterial blood pressure, are often more pronounced than those produced by traditional drugs intravenously administered to induce anesthesia (1)(2)(3)(4)(5). Thirty-six ASA I and I1 patients who received no premedication were studied.…”
mentioning
confidence: 99%
“…Our experimental data (in the cat) indicate that the increase in HR is a direct effect of the drug and not related to baroreflex mechanisms (23). The effects of methohexital on the heart and systemic vascular resistance seem to vary according to dose but above all depending on the populations of patients studied (22,(24)(25)(26)(27). Very high infusion rates (24 mg * kg-'h-I) in neurosurgical patients were associated with a 24% reduction in SVR and no change in CO (26).…”
Section: Discussionmentioning
confidence: 79%